2012
DOI: 10.1111/gbi.12012
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐ to nanostructure and geochemistry of extant crinoidal echinoderm skeletons

Abstract: This paper reports the results of micro- to nanostructural and geochemical analyses of calcitic skeletons from extant deep-sea stalked crinoids. Fine-scale (SEM, FESEM, AFM) observations show that the crinoid skeleton is composed of carbonate nanograins, about 20-100 nm in diameter, which are partly separated by what appears to be a few nm thick organic layers. Sub-micrometre-scale geochemical mapping of crinoid ossicles using a NanoSIMS ion microprobe, combined with synchrotron high-spatial-resolution X-ray m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 96 publications
(216 reference statements)
1
22
0
Order By: Relevance
“…Indeed, the laminated structure of the cidaroid spine composed of up to about 1-lm thick layers revealed by the slight etching (Fig. 3) is commonly observed among representatives of all echinoderm classes (e.g., Gorzelak et al, 2011Gorzelak et al, , 2013. It has been hypothesized that this lamination pattern must represent successive growth episodes (Dubois, 1991;Seto et al, 2004).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Indeed, the laminated structure of the cidaroid spine composed of up to about 1-lm thick layers revealed by the slight etching (Fig. 3) is commonly observed among representatives of all echinoderm classes (e.g., Gorzelak et al, 2011Gorzelak et al, , 2013. It has been hypothesized that this lamination pattern must represent successive growth episodes (Dubois, 1991;Seto et al, 2004).…”
Section: Discussionmentioning
confidence: 92%
“…6 in Gorzelak et al, 2011; fig. 1 in Gorzelak et al, 2013). The thickness of individual layers ranges from 0.7 to 1.2 lm (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In topography image, some nanogranules present a rim around them, with other topography indicating that the compositional variation is part of other phase or a mixing of phases. Several authors (Dauphin 2002;Cuif et al 2008;Gorzelak et al 2013) have studied these envelopes in recent and fossil organisms and proposed that they could be organic coatings from the original organic matrix.…”
Section: Nanostructural Characterisationmentioning
confidence: 99%
“…On the other hand, higher sulphur concentrations may indicate a greater content of organic material in the calcareous lattice (Lorens & Bender, 1980;Vander Putten et al, 2000). In calcitic shells of brachiopods, Cusack et al (2008) found sulphur in a form of sulphate and sulphur-containing amino acids (proteins), whereas Gorzelak et al (2013) recorded that in crinoids calcite sulphur was associated with sulphated polysaccharides. In addition, Gorzelak et al (2013) observed that high Mg concentrations in the skeleton were correlated with the distribution of sulphates, and this pattern agrees with our results (Fig.…”
Section: Discussionmentioning
confidence: 99%